Coupled‐Waveguides for Dispersion Compensation in Semiconductor Lasers. Issue 5 (15th March 2018) - Bidaux, Yves; Kapsalidis, Filippos; Jouy, Pierre; Beck, Mattias; Faist, Jérôme
Abstract: A dual waveguide for intracavity dispersion compensation in semiconductor lasers is presented and applied to a short mid‐infrared wavelength quantum cascade laser operating in the first atmospheric window ( λ ≈ 4.6 μm). As a result, stable comb operation on the full multi‐mode dynamical range is achieved in this device. Unlike previously proposed schemes, the dual waveguide approach can be applied to various types of semiconductor lasers and material systems. In particular, it could enable efficient group velocity dispersion compensation at near‐infrared wavelengths where semiconductor materials exhibit a large value of that parameter. Abstract : A dual waveguide for intracavity dispersion compensation in semiconductor lasers is presented and stable comb operation on the full dynamical range of the device is obtained. Unlike previously proposed schemes, the dual waveguide approach can be applied to various types of semiconductor lasers and material systems and could enable efficient group velocity dispersion compensation from near to far to infrared wavelengths.